Explore Westonci.ca, the leading Q&A site where experts provide accurate and helpful answers to all your questions. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To find [tex]\((g \circ f)(x)\)[/tex], we need to apply the function [tex]\(f(x)\)[/tex] first and then take the result and apply the function [tex]\(g\)[/tex] to that. Let's proceed step-by-step.
1. Define the function [tex]\(f(x)\)[/tex]:
[tex]\[ f(x) = 2x + 1 \][/tex]
2. Apply the function [tex]\(f(x)\)[/tex]:
[tex]\[ f(x) = 2x + 1 \][/tex]
3. Now, take the result of [tex]\(f(x)\)[/tex] (which is [tex]\(2x + 1\)[/tex]) and apply the function [tex]\(g\)[/tex] to it:
[tex]\[ g(x) = 6x + 2 \][/tex]
4. Replace [tex]\(x\)[/tex] in [tex]\(g(x)\)[/tex] with [tex]\(f(x)\)[/tex]:
[tex]\[ g(f(x)) = g(2x + 1) \][/tex]
5. Apply [tex]\(g\)[/tex] to [tex]\(2x + 1\)[/tex]:
[tex]\[ g(2x + 1) = 6(2x + 1) + 2 \][/tex]
6. Distribute and simplify:
[tex]\[ g(2x + 1) = 6 \cdot 2x + 6 \cdot 1 + 2 \][/tex]
[tex]\[ = 12x + 6 + 2 \][/tex]
[tex]\[ = 12x + 8 \][/tex]
Thus, the composition [tex]\((g \circ f)(x)\)[/tex] is:
[tex]\[ (g \circ f)(x) = 12x + 8 \][/tex]
1. Define the function [tex]\(f(x)\)[/tex]:
[tex]\[ f(x) = 2x + 1 \][/tex]
2. Apply the function [tex]\(f(x)\)[/tex]:
[tex]\[ f(x) = 2x + 1 \][/tex]
3. Now, take the result of [tex]\(f(x)\)[/tex] (which is [tex]\(2x + 1\)[/tex]) and apply the function [tex]\(g\)[/tex] to it:
[tex]\[ g(x) = 6x + 2 \][/tex]
4. Replace [tex]\(x\)[/tex] in [tex]\(g(x)\)[/tex] with [tex]\(f(x)\)[/tex]:
[tex]\[ g(f(x)) = g(2x + 1) \][/tex]
5. Apply [tex]\(g\)[/tex] to [tex]\(2x + 1\)[/tex]:
[tex]\[ g(2x + 1) = 6(2x + 1) + 2 \][/tex]
6. Distribute and simplify:
[tex]\[ g(2x + 1) = 6 \cdot 2x + 6 \cdot 1 + 2 \][/tex]
[tex]\[ = 12x + 6 + 2 \][/tex]
[tex]\[ = 12x + 8 \][/tex]
Thus, the composition [tex]\((g \circ f)(x)\)[/tex] is:
[tex]\[ (g \circ f)(x) = 12x + 8 \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.